Mother's Attitude and Role Related to Toilet Training Readiness in Toddler - Rahmawati, Aula; Indriati, Ganis; Deli, Hellena (jitek, 2022)
The toilet training readiness was influenced by various factors, such as the mother’s attitude, role, and the child's readiness. This study aimed to determine the correlation between mothers' attitudes and roles with toilet training readiness in toddlers. This study used a descriptive correlational design using a cross-sectional approach. The research sample was 96 respondents using an accidental sampling technique. The analysis used the chi-square test to identify the correlation between mothers' attitudes and roles with toilet training readiness in toddlers. The results of the study showed the mother's attitudes in the positive category (53.1%), the mother’s roles in the good category (54.2%) and toilet training readiness in the ready category (69.8%). The results of the chi-square test showed a correlation between mother's attitudes with toilet training readiness (p-value<0.001; alpha 0.05) and the correlation between mother's role and toilet training readiness (p-value0.001; alpha 0.05). This study shows a significant correlation between mothers' attitudes and roles with toilet training readiness in toddlers.